2016
DOI: 10.3389/fpsyg.2016.02044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Trauma Exposure and Depression among Adolescents after Earthquake: The Roles of Fear and Resilience

Abstract: Middle school students (N = 1435) were assessed 18 months after the Wenchuan earthquake using measures of trauma exposure, fear, resilience, and depression, to examine the effects of fear and resilience on the relationship between trauma exposure and depression. Fear mediated the relationship between trauma exposure and depression, whereas resilience moderated the relationship between fear and depression. These findings suggest that trauma exposure has a direct positive impact on depression, but also indirectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 80 publications
3
17
0
Order By: Relevance
“…The results confirmed the first hypothesis of the study showing that coronavirus fear functioned a mediating role between perceived coronavirus risk and parental coronavirus anxiety. Although there is no direct evidence concerning mediating role of fear in the context of pandemic, past research demonstrated that fear mediated the relationship between trauma severity and posttraumatic growth (Zhou et al, 2018) and trauma exposure and depression (Zhou et al, 2016). Consistent with our second hypothesis, our findings indicated that mental well-being moderated the relationship between coronavirus risk and parental coronavirus anxiety, suggesting that mental well-being buffers the effect of coronavirus risk on parental coronavirus anxiety.…”
Section: Discussionsupporting
confidence: 86%
“…The results confirmed the first hypothesis of the study showing that coronavirus fear functioned a mediating role between perceived coronavirus risk and parental coronavirus anxiety. Although there is no direct evidence concerning mediating role of fear in the context of pandemic, past research demonstrated that fear mediated the relationship between trauma severity and posttraumatic growth (Zhou et al, 2018) and trauma exposure and depression (Zhou et al, 2016). Consistent with our second hypothesis, our findings indicated that mental well-being moderated the relationship between coronavirus risk and parental coronavirus anxiety, suggesting that mental well-being buffers the effect of coronavirus risk on parental coronavirus anxiety.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with previous studies assessing PTSD diagnosis (e.g., Tracy et al, 2011) and depressive symptoms (e.g., Zhou, Wu, & An, 2016) after disaster exposure, we anticipated positive associations between the number of Katrina-related traumatic events and the severity of PTSD and depression symptoms. We further expected that perceived social support would predict fewer depressive symptoms and cluster-specific PTSD symptoms, whereas displacement would be positively associated with these outcomes.…”
supporting
confidence: 82%
“…In this study, we found that compared with the low symptoms group, adolescents with more serious trauma exposure or those using more maladaptive cognition emotion regulation strategies were more likely to belong to both the mild and medium comorbid symptoms groups. Here, trauma exposure can challenge the stability of beliefs about individuals and the world, resulting in feelings of uncontrollability and unpredictability that in turn lead to negative emotions or malfunction adjustment, and thus may elicit PTSD (Janoff-Bulman and Frieze, 1983) and depression (Zhou et al, 2016). Maladaptive strategies may lead to a tendency in traumatized individuals to use negative thoughts and memories elicited by a negative mood to understand their current circumstances (Zhen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Zhen et al, 2016) and depression (e.g. Zhou et al, 2016). In addition, the emotional processing theory also suggests that exposure to trauma may lead victims to have negative cognition of self (e.g.…”
Section: Introductionmentioning
confidence: 99%